APPLICATION OF DIBR AND MAIRCA METHODS IN THE EVALUATION OF THE ECONOMIC PERFORMANCE OF THE ECONOMY OF BOSNIA AND HERZEGOVINA - Radojko Lukić (Economic Review)
The issue of analyzing factors of the dynamics of the economic performance of every economy, including Bosnia and Herzegovina (BiH), is continuously very current, challenging, significant, and complex. An adequate control of the key factors can significantly influence the achievement of the target economic performance of BiH’s economy. The application of multi-criteria decision-making methods enables an adequate control of the key factors of the economic performance of BiH’s economy. Bearing that in mind, this paper analyzes the dynamics of the economic performance of BiH’s economy in the period 2013 - 2022 based on the DIBR and MAIRCA methods. The top five years of the economic performance of BiH’s economy according to the DIBR and MAIRCA methods fall in the following order: 2021, 2022, 2018, 2019, and 2017. The worst economic performance in BiH’s economy was registered in 2020, which was contributed, among other things, by the Covid-19 pandemic. Generally speaking, the economic performance of BiH’s economy significantly improved recently. This was influenced by adequate management of the analyzed statistical variables (gross domestic product, inflation, agriculture, industry, export, import, capital, income, taxes, time required to start business – days, and domestic loans provided by the financial sector). The factors such as the geopolitical situation, the economic climate, foreign direct investments, the energy crisis, the digitalization of company's entire operation, the application of sustainable development concept and other others are also important. In any case, the adequate control of these variables can greatly influence the achievement of the target economic performance of BiH’s economy.